Alectinib continuation during COVID 19 'antiviral' treatment: Risk or benefit?. (July 2021) - Akkus, Mehmet Hadi; Kaman, Omur; Dogan, Mutlu
Introduction: Serious Acute Respiratory Syndrome Coronavirus 2 (SARSCoV2) has led to COVID 19 pandemic a year ago and it has not been globally taken under control yet. COVID 19 tends to have poorer prognosis in cancer patients. Additionally, we have no well-established guidelines for management of these patients during pandemic, in terms of treatment of 'cancer' and treatment of 'COVID 19'. Tyrosine kinase inhibitors (TKIs) are given without any break in cancer patients to have better survival outcomes in daily routine. However, there is no well-established data to continue or delay ALK inhibitors in lung cancer patients infected with SARS-CoV2. Concomittant use of ALK inhibitors and COVID 19 antiviral treatment is a dilemma because of the lack of data in this area. Case Report: A 47-year old female metastatic ALK positive nonsquamous cell lung cancer patient on alectinib, a second generation ALK inhibitor was diagnosed with symptomatic COVID 19. She was given favipiravir for COVID 19 while continuing alectinib. Management and outcome: The patient continued alectinib during COVID 19 antiviral treatment without any break. She tolerated 'concomittant' alectinib & favipiravir. She had partial remission after three months of alectinib without any dose adjustment despite active COVID 19 medication. Discussion: To best of our knowledge, this is the first case who continued alectinib without dose adjustment during antiviral COVID-19 medication without clinically worsening. There is limited data about 'concomittant' use of TKIs and antiviral COVID 19 medication in the literature. There are some case reports, but they generally tended to delay or suspend TKIs during COVID 19 antiviral medication. Our case differs from them in terms of continuation of alectinib without any break or additional side effects during favipiravir for symptomatic COVID 19. We consider that our case might contribute to the literature in terms of management of cancer patients on targeted therapy during COVID 19 antiviral treatment. However, clinical trials are needed in this area.